Effect of Ageing on Seed Quality Parameters in Brinjal Var. Anand Raj - K. M. Bera; Kalyanrao; M. M. Pandya; D. A. Patel; M. J. Jadav; J. S. Mahla (International Journal of Economic Plants)
The experiment was conducted during April, 2022–23 and April, 2023–24 at Department of Seed Science and Technology, B. A. College of Agriculture, AAU, Anand, Gujarat, India to study on the effect of seed accelerated ageing treatments on seed quality parameters of brinjal var. Anand Raj using the CRD design at Department of Seed Science and Technology, B. A. College of Agriculture, AAU, Anand, Gujarat, India. The seeds were aged with temperature 45˚C and 95 to 100% RH for various duration T1: 0 days, T2: 1 days, T3: 2 days, T4: 3 days, T5: 4 days during 2022-23, 2023-24. The data pertaining to seed quality attributes showed the non aged seeds (T1) showed positive response for all quality parameters and recorded significantly highest as germination (96.33%), seedling root length (4.66 cm), seedling shoot length (5.24 cm), seedling length (9.90 cm), seedling fresh weight (0.49 g), seedling dry weight (0.0403 g), seedling vigour index I (1009.38) and seedling vigour index II (3.87). Seed quality influenced by seed accelerated ageing duration significantly higher germination (94.67%), seedling root length (4.23 cm), seedling shoot length (4.86 cm), seedling length (9.09 cm) seedling fresh weight (0.42 g), seedling dry weight (0.0382 g), seedling vigour index I (894.67) and seedling vigour index II (3.60) was showed by T2: 1 days of ageing. Ageing is the irreversible damage to seed and more ageing duration and given temperature leads to damage and reduced seed quality and other quality parameter of brinjal seed.